Factorize

        x^2-81=(x-9)(x+9)        

        9a^2-25=(3a-5)(3a+5)        

        36y^2-121=(6y-11)(6y+11)        

        49a^2-100b^2=(7a-10b)(7a+10b)        

        (a+b^2 )-36=(a+b-6)(a+b+6)        

        16c^2-1=(4c-1)(4c+1)        

        1-64b^2=(1-8b)(1+8b)        

        \frac{9}{16}-25x^2=(\frac{3}{4}-5x)(\frac{3}{4}+5x)        

        z^2-\frac{1}{144}=(z-\frac{1}{12})(z+\frac{1}{12})        

        1-(a-b)^2=(1-a+b)(1+a-b)        

    \\    

       (3m-n)^2-(m-2n)^2       

        = [(3m-n)-(m-2n)][(3m-n)+(m-2n)]       

       = (3m-n-m+2n)(3m-n+m-2n)       

       = (2m+n)(4m-3n)       

    \\    

       (3x+2y)^2-(2x-3y)^2       

       =[(3x+2y)+(2x-3y)][(3x+2y)-(2x-3y)]       

       =(5x-y)(x+5y)       

    \\    

       16(a+b)^2-9(a-b)^2       

       =[4(a+b)+3(a-b)][4(a+b)+3(a-b)]       

       =(a+7b)(7a+b)       

    \\    

       9(x+y)^2-16(x-2y)^2       

       =[3(x+y)-4(x-2y)][3(x+y)+4(x-2y)]       

       =(11y-x)(7x-5y)       

    \\    

       36(a-b)^2-25(a+b)^2       

        =[6(a-b)-5(a+b)][6(a-b)+5(a+b)]       

        =(6a-6b-5a-5b)(6a-6b+5a+5b)       

        =(a-11b)(11a-b)       

    \\    

       9(3x+1)^2-4(x-1)^2       

       = [3(3x+1)-2(x-1)][3(3x+1)+(x-1)]       

       = (9x+3-2x+2)(9x+3+2x-2)       

       = (7x+5)(11x+1)       

    \\    

       a^2-2ab+b^2-c^2       

       = (a-b)^2-c^2       

       = (a-b-c)(a-b+c)       

    \\    

       x^2-a^2-2a-1       

       = x^2-(a^2+2a+1)       

       = x^2-(a+1)^2       

       = (x-a-1)(x+a+1)       

    \\    

       x^2-m^2+6mn-9n^2       

       = x^2-(m^2-6mn+9n^2)       

       = x^2-(m-3n)^2       

       = (x-m+3n)(x+m-3n)       

    \\    

       a^4-b^4       

       = (a^2+b^2)(a^2-b^2)       

       = (a^2+b^2 )(a-b)(a+b)       

    \\    

       16a^4-81b^4       

       = (4a^2-9b^2)(4a^2+9b^2)       

       = (2a-3b)(2a+3b)(4a^2+9b^2 )       

    \\    

       3-75z^2       

       = 3(1-25z^2 )       

       = 3(1-5z)(1+5z)       

    \\    

       48a^2 b^2-3       

       = 3(16a^2 b^2-1)       

       =3(4ab-1)(4ab+1)       

    \\    

       4x^3-81x       

       = x(4x^2-81)       

       = x(2x-9)(2x+9)       

    \\    

       9b^3-144b       

       = b(9b^2-144)       

       = b(3b-12)(3b+12)       

    \\    

       32x^2-72y^2       

       = 2(16x^2-36y^2 )       

       = 2(4x-6y)(4x-6y)       

    \\    

       50x^2-32y^2       

       = 2y(25x^2-16y^2 )       

       = 2y(5x-4y)(5x+4y)       

    \\    

       a^3-4ab^2       

       = a(a^2-4b^2)       

       = a(a-2b)(a+2b)       

    \\    

       ab^3 c-abc^3       

        = abc(b^2-c^2 )       

       = abc(b-c)(b+c)       

    \\    

       9(x+y)^3-16(x+y)       

       = (x+y)[9(x+y)^2-16]       

       = (x+y)(3x+3y-4)(3x+3y+4)       

    \\    

       1-0.49c^6       

       = (1-0.7c^3 )(1+0.7c^3 )       

    \\    

       x^2-y^2-8yz-16z^2       

       = x^2-(y^2+8yz+16z^2 )       

       = x^2-(y+4z)^2       

       = (x-y-4z)(x+y+4z)       

    \\    

       x^3 y^3-25xy/z^2       

       = xy(x^2 y^2-25/z^2 )       

       = xy(xy+5/2)(xy-5/2)       

    \\    

       324x^4-0.0064b^4       

       = 1/1000 (324x^4-64b^4 )       

       = 4/100 (81x^4-16b^4 )       

       = 4/100 (9x^2-4b^2 )(9x^2+4b^2 )       

       = 0.0004(3x-2b)(3x+2b)(9x^2+4b^2 )       

        or \ \ (0.09x^2+0.04b^2 )(0.3x+0.2b)(0.3x-0.2b)       

    \\    

Factorize

    82^2-18^2=(82+18)(82-18)=100 \times 64=6400    

    8^2-9.2^2=(15.8+9.2)(15.8-9.2)=25 \times 6.6=165    

    8^2-0.2^2=(0.8+0.2)(0.8-0.2)=1 \times .06=0.6    

    (7 \frac{3}{4})^2-(2 \frac{1}{4})^2=(7 \frac{3}{4}+2 \frac{1}{4})(7 \frac{3}{4}-2 \frac{1}{4})=10 \times 5 \frac{1}{2}=55    

    (6 \frac{4}{11})^2-(4 \frac{7}{11})^2=(6 \frac{4}{11}+4 \frac{7}{11})(6 \frac{4}{11}-4\frac{7}{11}) =11 \times 1 \frac{4}{11}=19    

    \frac{(7.3 \times 7.3-2.7 \times 2.7)}{(7.3-2.7)}=\frac{(7.3+2.7)(7.3-2.7)}{(7.3-2.7)}=10    

Advertisements